Antibiotic dispensing following pediatric visits in the US emergency departments and outpatient settings from 2006 to 2016. Issue 5 (27th August 2019) - Agiro, Abiy; Sridhar, Gayathri; Gordon, Aliza; Brown, Jeffrey; Haynes, Kevin
Abstract: This study measured rates and trends in antibiotic dispensing for emergency department (ED) and outpatient visits by age groups. This retrospective analysis used data from the National Institutes of Health Collaboratory Distributed Research Network. The analysis included children (aged > 3 months to <12 years) and adolescents (aged 12 to <19 years) with or without an antibiotic dispensed within 3 days following visits for infectious diagnoses occurring from 2006 to 2016, with no antibiotic fills 90 days prior. Diagnoses were classified as: 1) respiratory tract infections (RTIs) for which antibiotics are mostly indicated; 2) RTIs for which antibiotics are mostly not indicated; 3) respiratory conditions for which antibiotics are never indicated; 4) infectious conditions beyond RTIs regardless of antibiotic indication. The largest annual decrease in any dispensed antibiotics (5% per year) was seen in ED visits for not indicated RTIs and never indicated respiratory conditions (incidence rate ratio [IRR] 0.95, 95% confidence interval [CI] 0.95‐0.96). In outpatient settings, a 2% per year decrease was seen for not indicated RTIs and never indicated respiratory conditions (IRR 0.98, 95% CI 0.98‐0.98). Broad‐spectrum antibiotics had a 1% per year increase in outpatient settings for mostly indicated RTIs (IRR 1.01, 95% CI 1.01‐1.01). Compared with adolescents, broad‐spectrum antibiotic dispensing rates and trends were consistently higher for children regardless of diagnosis or care setting. Using national claims data, this real‐world analysis found uneven decreases in potentially inappropriate antibiotic dispensing, suggesting the need for antibiotic stewardship interventions to become more common in outpatient settings.